Research on the Influence of Tractor Parameters on Shift Quality, Based on Uniform Design - Junyan Wang; Changgao Xia; Xin Fan; Junyu Cai (Applied Sciences, 2022)
This paper mainly studies the influence of tractor parameters on shift quality. The kinetic theoretical model of the powertrain system was deduced, and then the simulation model was established by using AMESim simulation software. The acceptable jerk and shift time were selected as the evaluation indexes of shift quality. The influence of engine speed, the tractive resistance of the tractor, the clutch oil pressure and the orifice diameter on the above evaluation indexes were quantitatively studied. The simulation test, under the influence of a single parameter, was carried out using the parameter analysis method. After this, the uniform design experimentation method was used to carry out the simulation test, under the influence of combined parameters. The results showed that in order to improve the shift quality, it is necessary to focus on the selection of clutch oil pressure and orifice diameter.